Second order nonlinear optical activity of amino acids, guanidines and pyridinium salts of inorganic anions - Ayeah, Vera (2019)
The present work is committed to organic nonlinear optical materials (NLO materials) and their prospective applications. The literary part consists of the theoretical background of organic NLO materials. Properties of organic and inorganic compounds as NLO materials are compared and the reason why most commercial NLO products are inorganic compounds despite the numerous and better NLO properties of organic molecules over inorganic molecules is justified. Characteristics of good NLO crystals such as phase matchability, wide optical transparency second order nonlinear susceptibility, thermal and chemical stability, availability of large single crystals and environmental stability, high second harmonic generation (SHG) efficiency, high mechanical strength and high laser damage resistance are discussed in detail. Second order nonlinear optical phenomena for instance SHG, optical mixing and optical parametric oscillation are considered. Attention is paid to amino acid based compounds and quanidine compounds as organic NLO materials. In the experimental part, pyridinium salts of inorganic anions were synthesized and the structures of the products were identified with the help of 1H NMR spectroscopy and Xray crystallography. The inorganic acids used during the synthesis are HBF4, H3PO4, HNO3 and H2SO4. Synthesis with H2SO4 was carried out twice in 1:1 and 1:2 molar ratios with the pyridine compounds. The SHG efficiencies of the synthesized compounds were investigated using the Kurtz and Perry powder method. Compounds 26, 28, 30, 32, 35, 39, 44, 46 and 50 showed some NLO activity by displaying some SHG efficiencies with intensities about 1-5% that of urea reference.